Relationship between Financial Income Tax Reform and Implicit Tax: Case of South Korean Bond Market - Lee, Sang-Yeob; Yoon, SungMan (Asian Economic and Financial Review, 2019)
In South Korea, comprehensive taxation, which is a combination of income from various sources, has been applied to financial income exceeding a certain amount. However, criticism continues to be raised that the level of financial income is lower compared with other incomes, and South Korea’s taxation authorities lowered the standard amount in 2013, thereby increasing the tax burden on financial income. This study aims to analyze the response of the bond market to the reduction of the standard amount of comprehensive taxation for financial income. This study analyzes the implicit tax phenomenon that the pre-tax return of bonds with large tax benefits is relatively low, in Korean bond market. It suggests that the sustainability level of the bond market has increased as the difference between the yield of the National Housing Bond, which has a large tax burden after 2013, and that of the general Korean Treasury Bond has decreased to a statistically significant level. Therefore, this study proposes that tax reforms on financial income may affect not only the level of tax burden but also the macro-economy of money transfers among financial instruments and financial markets.